النوازل المعاصرة المتعلقة بالمساجد - ببوخة, عفيفة; سعيد, كوكب (جامعة الوادي university of eloued, 2023)
"موضوع المذكرة موسوم ب:"" النوازل المتعلقة بالمسجد""، وإشكاليّتُه الرئيسية تبحث عن بيان حكم ماجدّ من المسائل مما لم يكن معروفا عند المتقدمين أو طرأ عليها بعض التغيرات وتضمن نماذج مختارة، فجاء هذا البحث ليبيّن حكم هاته النوازل. وقد جعلناه في مقدمة وأربعة مباحث: المبحث التمهيدي حددنا خلالَه تعريف النوازل، والمسجد وتصنيفاته ومراحل عمارته، والمباحث الثلاثة الأخرى للنماذج التطبيقية، في كل مبحث أربع مسائل، والتي صنفّناها باعتبار البناء الخارجي المسجد وداخله وبعض الأعمال التي تقام فيه، حوى المبحث الأول النوازل المتعلقة بخارج المساجد، وأمّا المبحث الثاني: النوازل المتعلقة بداخل المساجد، وأخيرا المبحث الثالث: النوازل المتعلقة بالأعمال التي تقام في المسجد. وقد توصلنا إلى مجموعة من النتائج؛ أهمها أن أحكام المسائل المدروسة تندرج ضمن قاعدة ""لا ينكر تغير الأحكام بتغير الأزمان"" نبهنا إلى توصيات أبرزها: الاهتمام بفقه النوازل في كلية الشريعة، تدريسا وبحثا، وإقامة دورات من أساتذة متخصصين في دراسة النوازل. ""The subject of the thesis is titled by: ""moderncatarrh related to the Mosque"", and its main problem is to seek a statement of Majid's decision on matters which were not known to the candidates or on which certain changes occurred through selected models, so this research came to show the decision of these and we established into introduction of four research section: preliminary section focused on definition of Calamities and the mosque classifications and its architectural stages. On the other hand, the rest of the three research section focused on the model applications, where each research section contain four questions, which classified such as the outside of the mosque, inside of the mosque, and the work in which it is held.In particular, the first research section contain the catarrh of outside of the mosque, the second research section contain the catarrh of inside of the mosque, and third research section contain the catarrh of and the work in which it is held.Consequently, we have reached to the results that discussed the correct judgment for the target questions. "
فقه
Keywords: المسجد، النوازل .المعاصرة.; the mosque, modern catarrh